New Computing Technology in Reliability Engineering - Bris, Radim; Domesova, Simona (Mathematical problems in engineering, 2014)
Reliability engineering is relatively new scientific discipline which develops in close connection with computers. Rapid development of computer technology recently requires adequate novelties of source codes and appropriate software. New parallel computing technology based on HPC (high performance computing) for availability calculation will be demonstrated in this paper. The technology is particularly effective in context with simulation methods; nevertheless, analytical methods are taken into account as well. In general, basic algorithms for reliability calculations must be appropriately modified and improved to achieve better computation efficiency. Parallel processing is executed by two ways, firstly by the use of the MATLAB function parfor and secondly by the use of the CUDA technology. The computation efficiency was significantly improved which is clearly demonstrated in numerical experiments performed on selected testing examples as well as on industrial example. Scalability graphs are used to demonstrate reduction of computation time caused by parallel computing.